Speaking Science to Law Toward a Multidimensional and Actor-Centric Framework (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The picture sketched here rests upon a deep and wide-ranging transformation in both the methods and paradigms that structure the exercise of power. It also constitutes an invitation to interdisciplinary communities of scholars and practitioners to engage in empirically grounded and forward-looking discussions about the sources of legitimacy upon which democratic institutions should rely when adopting laws, which are paradigmatic and foundational acts of authority and power.
Keywords: sciences; expertise; normativity; legitimacy; innovation